The Analysis of Students’ Perception of Virtual English Learning: A case Study of MyBest LMS Implementation - Mike Amelia; Silvia Nanda Putri Erito; Surtika Ayumida (English Language Education Department, Universitas Majalengka, 2024)
This study aims to analyze students' perceptions of the implementation of MyBest LMS in virtual English learning. The analysis uses Technology Acceptance Model (TAM). In the context of English learning in the Information Systems study program at Bina Sarana Informatika University, E-Learning has become an increasingly important tool to facilitate the lecture process. Through the LMS platform commonly referred to as MyBest, students can access learning materials, assignments, discussions, and evaluations online, without being limited by time and space. However, success in its implementation is not only determined by the sophistication of the technology used, but also by the user's perception of the platform. In this context, students' perception towards E-Learning has an important role in determining the effectiveness and acceptance of the technology in the learning process, especially in English learning which is one of the courses conducted virtually at UBSI. This research uses descriptive method by using observation, questionnaire and interview collected from 40 Information System students of Bina Sarana Informatika University who were selected from cluster random sampling technique.